Taxonomy of some Boreoheptagyiini Brundin (Diptera: Chironomidae: Diamesinae) from the mountains of Central Asia and the Middle East, with description and DNA barcoding of new taxa - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2020)
Chironomids of the tribe Boreoheptagyiini from the mountains of Iran, China and East Kazakhstan are revised using both morphological characters and partial DNA sequences of the mitochondrial cytochrome c oxidase subunit I gene. Using adult males, Palatovia lorestanica gen. nov. sp. nov., as well as Boreoheptagyia iranica sp. nov. both from Iran (Lorestan Province, Zagros Mountains), B. joeli sp. nov. from China (Tien Shan Mountains), and B. sarymsactyensis sp. nov. from Eastern Kazakhstan (Kazakh Mountain Altai), are described and figured. A brief redescription of the rare species B. brevitarsis (Tokunaga) from Iran (Mazandaran Province), previously known only from Japan, is also given. The DNA barcoding analysis shows well-supported genetic divergence between all studied taxa (four species of the genus Boreoheptagyia and one of Palatovia). Combining DNA barcodes obtained in this study with available sequences in GenBank, the phylogenetic relationships of the tribe Boreoheptagyiini are reconstructed. In the resulting Bayesian and maximum likelihood (ML) tree the polyphyly of the genus Boreoheptagyia is recognized. B. iranica is placed as a sister species to P. lorestanica, despite the lack of confirmation of their morphological similarity.